Area Moment of Inertia for Comparison of Implant Cross-Sectional Geometry and Bending Stiffness - Muir, P.; Johnson, K. A.; Markel, M. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Area moment of inertia for an object can be calculated by use of mathematical equations, and is defined by the dimensions of the object. Area moment of inertia and modulus of elasticity are principal factors determining bending stiffness. Because the majority of veterinary orthopaedic implants are made of 316L stainless steel, and therefore have a similar modulus of elasticity, comparison of area moment of inertia for different implants provides an estimate of relative bending stiffness and can assist implant selection for a particular fracture. Knowledge of this parameter may help avoid treatment complications, such as implant failure.
Keywords: Area moment of inertia; Bending stiffness; Orthopaedic implants